Meaning of life and spirituality in institutionalized elderly (Research, Society and Development, 2020)
The study aimed to understand how the elderly in two Long Term Care Facilities for the Elderly (LTCFs) experience daily spirituality and the meaning of life. This is a qualitative descriptive study, with an intentional sample of 14 elderly people, of both sexes, in private institutions in the city of Niterói / RJ. Three instruments were used for data collection: the institution's characterization form, the participant's characterization form and the interview script. Quantitative data were analyzed using descriptive statistics and qualitative data were analyzed according to the empirical-comprehensive model proposed by Amedeo Giorgi. The interpretation took place from the existentialist perspective of Frankl and Merleau-Ponty. In the analysis, three categories emerged: Aging at LTCFs, Spirituality as a support for institutionalized life, and Meaning of Life for the elderly in the institutional environment. The study concluded that spirituality and the meaning of life in the LTCF environment are important elements for facing the difficulties that the elderly experience in the institutional environment. The participants' speeches referred to adaptation, overcoming and emotional loneliness. There are many challenges experienced daily by the elderly population in the institutional environment, but the elderly can overcome them by finding their own meaning in life, combining the process of spirituality, which can be cultivated daily in the walk of those who so desire, favoring the meeting a satisfying life, even in an institutionalized environment and in the midst of constant need, especially in the presence of family members.